Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
If you multiply the second equation by 3, it becomes:
15x - 6y = 42
Then add the two equations together:
3x + 6y = -6
15x - 6y = 42
+
18x = 36
x = 2
substitute x back into the first equation:
3(2)+6y = -6
6 + 6y = -6
6y = -12
y = -2
So x=2,y=-2
15x - 6y = 42
Then add the two equations together:
3x + 6y = -6
15x - 6y = 42
+
18x = 36
x = 2
substitute x back into the first equation:
3(2)+6y = -6
6 + 6y = -6
6y = -12
y = -2
So x=2,y=-2
[tex] \left \{ {{3x+6y=-6} \atop {5x-2y=14\ \ | *3}} \right. \\\\ \left \{ {{3x+6y=-6} \atop {15x-6y=42}} \right.\\\+-----\\Addition\ method\\\\
18x=36\ \ \ | divide\ by\ 18\\\\x=2\\\\2y=5x-14\\\\
y=\frac{5x-14}{2}=\frac{5*2-14}{2} =\frac{10-14}{2}=-2\\\\Solution\\ \left \{ {{y=-2} \atop {x=2}} \right. [/tex]
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.